(untitled) (Research, Society and Development, 2023)
Increasingly, distributed generation is becoming a common practice, finding application both in homes and commercial establishments and in centralized generation facilities, such as large photovoltaic plants. The main objective is to propose the Solar Energy 4.0 platform to boost the integration between entrepreneurship, innovation and sustainability in the context of the implementation of photovoltaic solar energy plants. The training of qualified professionals and the creation of specialized companies can benefit the local economy, generating job opportunities and contributing to the socioeconomic development of communities. In the current context, photovoltaic solar energy represents a significant part of Brazil’s Gross Domestic Product (GDP), and this proposal aims to further strengthen this rapidly growing sector. The proposal seeks to meet this growing demand, enabling entrepreneurs and professionals in the renewable energy sector to adopt sustainable and innovative approaches in their photovoltaic projects. To achieve this objective, a management platform is presented that will allow the efficient planning, execution and monitoring of solar projects. The methodology was based on a bibliographical review of a narrative nature, and a systematic search was carried out for books, scientific articles and online journals published between the period 2013 and 2023, in the CAPES and Google Scholar periodical databases, which address the issue of solar energy today and the prospects after the implementation of new regulations for consumers and generators of photovoltaic solar energy. Among the results, we seek to align entrepreneurship, innovation and sustainability in the management of photovoltaic solar energy projects. With the proposed management platform and the training of professionals, it is expected to boost the growth of the solar energy sector, contributing to a more sustainable and economical future.